2022
DOI: 10.3390/nano12121981
|View full text |Cite
|
Sign up to set email alerts
|

Strong Tribocatalytic Nitrogen Fixation of Graphite Carbon Nitride g-C3N4 through Harvesting Friction Energy

Abstract: Mechanical energy derived from friction is a kind of clean energy which is ubiquitous in nature. In this research, two-dimensional graphite carbon nitride (g-C3N4) is successfully applied to the conversion of nitrogen (N2) fixation through collecting the mechanical energy generated from the friction between a g-C3N4 catalyst and a stirring rod. At the stirring speed of 1000 r/min, the tribocatalytic ammonia radical (NH4+) generation rate of g-C3N4 can achieve 100.56 μmol·L−1·g−1·h−1 using methanol as a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…of the piezocatalytic dye decomposition ratio is the excessive ZnO content acting as the recombination center rather than as the charge separation role in the BiFeO 3 /ZnO heterostructures. 38,41,42 To compare the reaction kinetics of the BiFeO 3 /ZnO heterostructures in different ZnO contents, the pseudo first order kinetic equation is investigated in eqn (2): 43,44 ln…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of the piezocatalytic dye decomposition ratio is the excessive ZnO content acting as the recombination center rather than as the charge separation role in the BiFeO 3 /ZnO heterostructures. 38,41,42 To compare the reaction kinetics of the BiFeO 3 /ZnO heterostructures in different ZnO contents, the pseudo first order kinetic equation is investigated in eqn (2): 43,44 ln…”
Section: Resultsmentioning
confidence: 99%
“…To compare the reaction kinetics of the BiFeO 3 /ZnO heterostructures in different ZnO contents, the pseudo first order kinetic equation is investigated in eqn (2): 43,44 …”
Section: Resultsmentioning
confidence: 99%
“…In future, there is hope of further enhancing the pyro-catalysis performance of the 2D organic g-C 3 N 4 catalyst through building a heterojunction structure to increase the separation of pyroelectrically induced positive and negative charges [ 44 , 45 , 46 , 47 ]. Besides the pyro-catalysis for harvesting environmental cold–hot thermal energy, the 2D organic g-C 3 N 4 nanosheet catalyst materials can be also designed to harvest mechanical energy to drive a chemical catalysis reaction [ 48 , 49 ]. The 2D organic g-C 3 N 4 catalyst nanomaterials have been reported as having an excellent piezocatalytic performance [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 2D organic g-C 3 N 4 catalyst nanomaterials have been reported as having an excellent piezocatalytic performance [ 48 ]. In our previous report, we have also found that the 2D organic g-C 3 N 4 could exhibit a strong tribocatalytic performance for nitrogen fixation through harvesting environmental friction energy [ 49 ]. It has the potential to obtain the enhanced catalytic dye decoloration performance of the 2D organic g-C 3 N 4 nanosheet catalyst nanomaterials by harvesting both the environmental cold–hot temperature alternation thermal-energy and the ordinary mechanical friction energy and vibration energy on basis of the synergy of muti-catalysis in future [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…67,68 N 2 can be converted to NH 3 by stirring g-C 3 N 4 catalyst and methanol solution with a PTFE magnetic bar at 1000 rpm. 69 After the friction between g-C 3 N 4 and PTFE magnetic bar, PTFE gained electrons while g-C 3 N 4 lost electrons (Fig. 14c).…”
Section: Applications Of Tribocatalysismentioning
confidence: 96%